Data Sharing: A Case Study of Luxury Surveillance by Tesla - Schuilenburg, Marc; Eski, Yarin (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
Why do people voluntarily give away their personal data to private companies? In this paper, we show how data sharing is experienced at the level of Tesla car owners. We regard Tesla cars as luxury surveillance goods for which the drivers voluntarily choose to share their personal data with the US company. Based on an analysis of semi-structured interviews and observations of Tesla owners’ posts on Facebook groups, we discern three elements of luxury surveillance: socializing, enjoying, and enduring. We conclude that luxury surveillance can be traced back to the social bonds created by a gift economy.